2013
DOI: 10.1123/jsr.2013.tr7
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability and Validity of Isometric Knee-Flexion and -Extension Measurement Using 3 Methods of Assessing Muscle Strength

Abstract: Context: Physicians and clinicians need portable, efficient, and cost-effective assessment tools to determine the effectiveness of rehabilitation programs after knee injury. Progress in rehabilitation should be evaluated using valid and reliable measurement methods. Objective: To examine the test-retest reliability of portable fixed dynamometry (PFD), handheld dynamometry (HHD), and isokinetic dynamometry (IKD). In addition, the authors sought to examine the validity of PFD and HHD by comparing differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 9 publications
3
78
1
Order By: Relevance
“…Maximal voluntary contraction of the quadriceps was expressed in terms of torque (newton meters), as calculated from the force through a lever arm. This type of evaluation is highly reliable, with intraclass correlation coefficients (ICCs) of 0.92 to 0.95 12 , 30 …”
Section: Methodsmentioning
confidence: 99%
“…Maximal voluntary contraction of the quadriceps was expressed in terms of torque (newton meters), as calculated from the force through a lever arm. This type of evaluation is highly reliable, with intraclass correlation coefficients (ICCs) of 0.92 to 0.95 12 , 30 …”
Section: Methodsmentioning
confidence: 99%
“…An HHD provides reliable and reproducible results when used for the evaluation of muscle groups that produce little or moderate amounts of force. However, the results obtained for strong muscles, such as the knee extensors, are less convincing26,27,28 ) . A systematic review comparing muscle strength assessment by HHD and isokinetic testing29 ) showed a positive correlation between these methods.…”
Section: Introductionmentioning
confidence: 99%
“…While the isokinetic dynamometer is considered the gold standard tool for isometric force assessment, it is a large, stationary, and expensive apparatus that is frequently unavailable to clinicians (Ordway, Hand, Briggs, and Ploutz Snyder, 2006;Toonstra and Mattacola, 2013). A hand-held dynamometer (HHD) is a convenient, relatively cheap portable tool that requires little training and can be easily applied in the clinic for strength assessment.…”
Section: Introductionmentioning
confidence: 99%